Characterization of the mannosyltransferase RV3779, which forms polyprenyl phosphomannose for the biosynthesis of phosphatidylinositol mannoside and lipoarabinomannan, and elucidation of the polymerization stages of galactan biosynthesis in mycobacteria - Scherman, Hataichanok, author; Brennan, Patrick J., advisor (Colorado State University. Libraries, 2008)
The cell wall complex of mycobacteria, dominated by highly unique structural polysaccharides and a rather impermeable layer of lipids, can give these bacteria the ability to resist the immune response and cause a prolonged and deadly illness. Various lipoglycans and glycolipids in the cell wall complex of mycobacteria, such as lipoarabinomannan (LAM), as well as the synthetic precursors of LAM; lipomannan, and the phosphatidyl myo-inositol mannosides, are essential for the normal growth and viability of mycobacteria, although the specifics of their synthesis are still not fully defined. Their synthesis are governed by a myriad of enzymes, including a class of enzymes called glycosyltransferases, which are one of the most diverse and important groups of enzymes in nature. A particular glycosyltransferase, Rv3779, is the primary focus of this study, and from sequence and bioinformatic analysis, we identified it as a putative mannosyltransferase belonging to the GT-C superfamily found to be involved in various aspects of synthesis of the higher forms of the phosphatidyl myo-inositol mannosides and the subsequent lipoglycans. Rv3779 is present in a prominent gene cluster involved in cell wall biosynthesis. From the experimental evidence gathered from construction and analysis of a Rv3779 knockout mutant of M. tuberculosis, the in vitro assay of the membrane fractions of an Rv3779-overexpressed strain of M. smegmatis, and analysis of the reaction products by thin layer chromatography and mass spectrometry, we have concluded that Rv3779 possesses polyprenyl phosphomannose synthase activity in a homologous manner to Ppm1. Polyprenyl phosphomannose is the key mannosyl donor that is utilized heavily by later enzymes in the extracytoplasmic hypermannosylation of the higher forms of these lipoglycans. The galactan chain serves as the covalent attachment point for mycolated arabinan and is a central structural polymer in the cell wall complex that is the second focus of this study. The exact stages of the buildup galactan are not fully elucidated, and involve unique polymerization steps. We have utilized various organic extraction and analytical techniques from a cell-free assay utilizing UDP-D-galactofuranose as a donor and the results of these studies suggest that the galactan chain is polymerized one galactofuranosyl residue at a time.
Keywords: arabinogalactan; lipoarabinomannan; mannosyltransferase; mycobacteria; Rv3779; microbiology